2017
DOI: 10.1371/journal.pgen.1006845
|View full text |Cite
|
Sign up to set email alerts
|

p53 and TAp63 participate in the recombination-dependent pachytene arrest in mouse spermatocytes

Abstract: To protect germ cells from genomic instability, surveillance mechanisms ensure meiosis occurs properly. In mammals, spermatocytes that display recombination defects experience a so-called recombination-dependent arrest at the pachytene stage, which relies on the MRE11 complex—ATM—CHK2 pathway responding to unrepaired DNA double-strand breaks (DSBs). Here, we asked if p53 family members—targets of ATM and CHK2—participate in this arrest. We bred double-mutant mice combining a mutation of a member of the p53 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 74 publications
3
66
1
Order By: Relevance
“…Altered DSB locations and formation of clustered DSBs may also contribute to asynapsis. Cells with synaptic defects die in pachytene from a recombination checkpoint, sex body failure, or both (Royo et al, 2010;Marcet-Ortega et al, 2017). We further surmise that some pachytene cells die from persistent DSBs (evidenced by γH2AX flares and recombination protein foci) even though they achieve full synapsis.…”
Section: Ankrd31 In Male and Female Fertilitymentioning
confidence: 65%
See 1 more Smart Citation
“…Altered DSB locations and formation of clustered DSBs may also contribute to asynapsis. Cells with synaptic defects die in pachytene from a recombination checkpoint, sex body failure, or both (Royo et al, 2010;Marcet-Ortega et al, 2017). We further surmise that some pachytene cells die from persistent DSBs (evidenced by γH2AX flares and recombination protein foci) even though they achieve full synapsis.…”
Section: Ankrd31 In Male and Female Fertilitymentioning
confidence: 65%
“…This result, along with elevated numbers of DMC1, RAD51, and RPA foci (Figures 3F-H), suggests that many cells contain a larger than usual number of incompletely repaired DSBs. Persistent DSBs at pachynema can trigger spermatocyte apoptosis (Pacheco et al, 2015;Marcet-Ortega et al, 2017), so this may account for some of the partially penetrant pachytene death in Ankrd31 -/mutants.…”
Section: Ankrd31 Deficiency Causes Dysregulated Recombinationmentioning
confidence: 99%
“…In addition, meiotic cells can be eliminated during prophase by a separate DNA damage checkpoint including ATM, CHK2 and the DNA damage response proteins p53 or p63 [17][18][19][20]23 . In line with the presence of such a checkpoint, we find a clear upregulation of TP63 (but not TP53) in human type I arrest spermatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Also in mouse oocytes, which do not contain a Y-chromosome or XY-silencing, the DNA damage checkpoint leads to specific activation of p63 20 . Moreover, it has been recently found that p53 and p63 are specifically involved in recombination-dependent mouse pachytene spermatocyte arrest 23 . We therefore propose that human type I spermatocyte elimination can be induced by a DNA damage signaling cascade that activates p63.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation